2016
DOI: 10.1161/jaha.116.003485
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Impact of Right Ventricular Pacing on Left Ventricular Systolic Function in Pacemaker Recipients With Preserved Ejection Fraction: Results From a Large Single‐Center Registry

Abstract: BackgroundThere is limited evidence of long‐term impact of right ventricular pacing on left ventricular (LV) systolic function in pacemaker recipients with preserved LV ejection fraction (LVEF). The objective of the study was to evaluate the outcome and echocardiographic course of baseline preserved LVEF in a large cohort of pacemaker recipients with respect to pacing indication and degree of right ventricular pacing.Methods and ResultsWe enrolled 991 patients (73±10 years, 54% male) with baseline normal (>55%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 31 publications
(67 reference statements)
1
33
1
1
Order By: Relevance
“…Similar findings were reported recently from a European single-center registry, which suggested that many patients with high-burden RV pacing maintain stable LVEF with a low incidence of new-onset HF. 25 It is likely that the adverse impact of RV pacing may affect individuals in a heterogeneous manner such that some may tolerate high RV pacing burden for many years without developing clinical HF, whereas others experience a rapid adverse impact, as noted in the acute phase of our study. Better tools are needed to identify which patients are most likely to experience a clinically relevant adverse effect of RV pacing on ventricular function.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Similar findings were reported recently from a European single-center registry, which suggested that many patients with high-burden RV pacing maintain stable LVEF with a low incidence of new-onset HF. 25 It is likely that the adverse impact of RV pacing may affect individuals in a heterogeneous manner such that some may tolerate high RV pacing burden for many years without developing clinical HF, whereas others experience a rapid adverse impact, as noted in the acute phase of our study. Better tools are needed to identify which patients are most likely to experience a clinically relevant adverse effect of RV pacing on ventricular function.…”
Section: Discussionmentioning
confidence: 77%
“…7,8,11,12 The inclusion of outpatient encounters in assessing the adverse impact of chronic RV pacing is particularly relevant given estimates that physician visits for HF account for ≈2% of all outpatient office visits and cost the healthcare system >$2 billion per year in the United States, representing an important opportunity for curbing healthcare expenditures. 27 Although it has been suggested that all patients undergoing pacemaker implantation with a predicted high burden of RV pacing should be implanted with a biventricular device, 7 the results of the PREVENT-HF study 28 and the preliminary results of the BioPace study 25,29 suggest that such a broad approach to biventricular pacing may not be justified. In general, patients with PICM seem to benefit from upgrade to biventricular pacing.…”
Section: Discussionmentioning
confidence: 99%
“…PPM and AVNA + DCCV resulted in an increase in AHI, central apnoeic events and ESS. Chronic ventricular pacing following AVNA can result in pacing‐induced dyssynchrony and impairment of left ventricular function and has been shown to exacerbate fluid shift to the upper airway overnight . In addition, the majority of the PPM and AVNA + DCCV patients (21/22) remained in AF at 6‐month follow‐up and therefore did not experience the haemodynamic benefits of prolonged SR The reduction in overnight oxygenation is the likely explanation for the increase in ESS because increased desaturation overnight has been shown to correlate with ESS .…”
Section: Discussionmentioning
confidence: 99%
“…PPM and AVNA + DCCV resulted in an increase in AHI, central apnoeic events and ESS. Chronic ventricular pacing following AVNA can result in pacing-induced dyssynchrony and impairment of left ventricular function 27,28 and has been shown to exacerbate fluid shift to the upper airway overnight. 29,30 In addition, the majority of the PPM and AVNA + DCCV patients (21/22) remained in AF Baseline (in AF)…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, low LVEF has been shown to be both a precipitant of as well as a consequence of AF . While patients with preexisting LV systolic dysfunction experience high rates of LV dysynchrony with RVP, in patients with initially preserved LVEF clinically relevant decline in LV function after DC‐PPM implant is less common . In our study population, the majority of patients had relatively preserved LVEF prior to DC‐PPM and only a small proportion had a significant reduction in LVEF after implant.…”
Section: Discussionmentioning
confidence: 99%